Editorial. (24th March 2023) - Iosifidis, Petros
This issue consists of six articles that have already been published via Online First and two book reviews. These cover themes such as the sustainability of media business models, Audiovisual Media Services Directive (AVMSD) rules in the European Union, sport TV and public policy.